THE EFFECTS OF INQUIRY TRAINING LEARNING MODEL ASSISTED MIND MAP FOR CONCEPTUAL KNOWLEDGE AND SCIENCE PROCESS SKILLS - Resti Harahap; Prof. Motlan; Nurdin Bukit (Universitas Negeri Medan, 2017)
This research aimed to analyze : (1) the students’ conceptual knowledge by using inquiry training learning model assisted mind map were better than using convensional learning, (2) the students’ science process skills by using inquiry training learning model were better than using convensional learning. This research carried out by a quasi-experimental and desaign was two group pretes-postest desaign.The population of this study was class X SMA IT As-Syafiiyah Medan. Sample selection was done by total sampling. Sample devided two class, eksperimen class by using inquiry training learning model and control class by using convensional. The instruments of this study used test conceptual knowledge and science process skills test in the form of a observations which were valid. The data were analyzed by using independent sample t-test. Conceptual knowledge postest results of experimental class is 75,20 and the control class is 56.87. Science process skills postest results of experimental class is 72,93 and the control class is 66,50. The result indicates the conceptual knowledge and KPS of students using inquiry training model assisted mind map is better than using convensional learning.